The kaleidoscope of autoimmunity: Multiple autoimmune syndromes and familial autoimmunity (2007)
Three related lines of evidence sustain the common origin for autoimmune diseases (ADs). First, the clinical evidence corresponding to the kaleidoscope of autoimmunity, which is the co-occurrence of various ADs within an individual or co-occurrence within members of a nuclear family. Second, the physiopathologic evidence indicating that the pathologic mechanisms might be similar among ADs. Lost, the genetic evidence indicating that autoimmune phenotypes could represent pleiotropic outcomes of nonspecific disease genes. The two conditions that better illustrate the kaleidoscope of autoimmunity are multiple autoimmune syndromes and familial autoimmunity. The multiple autoimmune syndromes consist of the presence of three or more well-defined autoimmune conditions in a single patient. The familial autoimmunity is defined as the presence of diverse ADs on multiple members of a nuclear family. Herein, both the multiple autoimmune syndromes and familial autoimmunity are discussed and various epidemiological factors considered in the context of the common genetic background of autoimmunity. © 2007 Future Drugs Ltd.